Beyond cognitive dysfunction: Relevance of ecological validity of neuropsychological tests in multiple sclerosis. (September 2019) - Weber, Erica; Goverover, Yael; DeLuca, John
In neurological diseases such as multiple sclerosis (MS), a neuropsychological assessment is often requested to assist clinicians in evaluating the role of cognition in a patient's level of everyday functioning. To be effective in this charge, it is assumed that performance on neuropsychological tests is related to how a person may function in everyday life, and the question is often asked: "Are neuropsychological tests ecologically valid?" In this review, we synthesize the literature that examines the use of neuropsychological tests to assess functioning across a variety of everyday functioning domains in MS (i.e. driving, employment, instrumental activities of daily living (IADLs)). However, we critically examine the usefulness of asking this broad question regarding ecological validity, given the psychometric and conceptual pitfalls it may yield. While many neuropsychological tests may be generally considered "ecologically valid" in MS, it is much more helpful to specify for whom, under what circumstances, and to what degree .